How to Get to the Distal Posterior Tibial Malleolus? A Cadaveric Anatomic Study Defining the Access Corridors Through 3 Different Approaches. Issue 4 (April 2017) - Assal, Mathieu; Dalmau-Pastor, Miki; Ray, Adrien; Stern, Richard
Abstract : Objective: Our objective is to review the anatomy and exposure of the posterior column and posterior tibial malleolus (the posterior tibial plafond) by defining the access corridors through 3 different approaches—posteromedial, posterolateral, and modified posteromedial. Methods: Cadaveric dissection with percentage of posterior tibial malleolus exposed, and strain gauge measurements to evaluate traction on the neurovascular bundle. Results: The 3 different approaches are applicable for exposure of different portions of the distal posterior tibial malleolus. Strain gauge measurements reveal the least traction on the flap containing the neurovascular bundle with the modified posteromedial approach (7.0 N) compared with the posteromedial (21.5 N) and posterolateral (16.8 N) approaches. Exposure of the posterior tibial malleolus was greater with the modified posteromedial approach (91%) compared with the other 2 approaches (posteromedial = 64%, posterolateral = 40%). Conclusions: Depending on the location of the principal fracture fragments, particularly in high energy ankle and pilon fractures, each of the posterior approaches has its indication, with the modified posteromedial approach revealing more of the posterior anatomy than the other 2 approaches. The latter approach places the least traction on the flap containing the neurovascular bundle.